Chemoproteomics‐Enabled De Novo Discovery of Photoswitchable Carboxylesterase Inhibitors for Optically Controlled Drug Metabolism. (7th December 2020) - Dwyer, Brendan G.; Wang, Chao; Abegg, Daniel; Racioppo, Brittney; Qiu, Nan; Zhao, Zhensheng; Pechalrieu, Dany; Shuster, Anton; Hoch, Dominic G.; Adibekian, Alexander
Abstract: Herein, we report arylazopyrazole ureas and sulfones as a novel class of photoswitchable serine hydrolase inhibitors and present a chemoproteomic platform for rapid discovery of optically controlled serine hydrolase targets in complex proteomes. Specifically, we identify highly potent and selective photoswitchable inhibitors of the drug‐metabolizing enzymes carboxylesterases 1 and 2 and demonstrate their pharmacological application by optically controlling the metabolism of the immunosuppressant drug mycophenolate mofetil. Collectively, this proof‐of‐concept study provides a first example of photopharmacological tools to optically control drug metabolism by modulating the activity of a metabolizing enzyme. Our arylazopyrazole ureas and sulfones offer synthetically accessible scaffolds that can be expanded to identify specific photoswitchable inhibitors for other serine hydrolases, including lipases, peptidases, and proteases. Our chemoproteomic platform can be applied to other photoswitches and scaffolds to achieve optical control over diverse protein classes. Abstract : Here, we present a new chemoproteomic platform for the de novo discovery of photoswitchable serine hydrolase inhibitors. Using this platform, we identified highly potent and selective photoswitchable inhibitors of the drug‐metabolizing enzyme carboxylesterase and demonstrated the pharmacological application of our compounds by optically controlling the hydrolysis of an immunosuppressant drug.